Can someone help me with the proof here? How do I start the proof? How do I simplify $(\sum_{i=1}^k a_i(Y_i - E(Y_i))^2$?

I'd end up getting a large multiplication between each $a_i(Y_i - E(Y_i)$ making my calculation really long.

Are there any summation properties that may help me as I am probably unaware of them?

Thank you!


Be brave!

$$\begin{align}E\left[\left(\sum_{i=1}^k a_i(Y_i - E[Y_i])\right)^2\right] &= E\left[\sum_{i=1}^k \sum_{j=1}^k a_i a_j (Y_i - E[Y_i])(Y_j - E[Y_j])\right] \\ &= \sum_{i=1}^k \sum_{j=1}^k a_i a_j E\left[(Y_i - E[Y_i])(Y_j - E[Y_j])\right]. \end{align}$$

Now, what can you say about $E\left[(Y_i - E[Y_i])(Y_j - E[Y_j])\right]$ when $i \ne j$? (Hint: use independence.)


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.